SOSIOECONOMIC ASPECT OF AGRIBUSINESS AFFECTED DURING COVID-19 PANDEMIC - Mariyah Mariyah; Saripah Nurfilah; Dina Lesmana; Agung Enggal Nugroho (Universitas Padjadjaran, 2021)
Agribusiness is a business in the agricultural sector that consists of providing input, production, marketing, processing and supporting which are interrelated and many actors are involved. The research purpose was to determine the socioeconomic aspect of agribusiness affected during the Covid-19 pandemic based on general public perception. This research was conducted in June-July 2020 by distributing questionnaires online from 18 June 2020 to 30 June 2020 using google form. The total respondents who filled in were 87 people. It’s consists of academics, practitioners, and the general public. Data were analyzed using qualitative analysis with a Likert scale. The results showed that agribusiness during the Covid-19 pandemic was positively impacted with an average score of 114.6. Socioeconomic aspects that have been positively affected, among others local input is sought, local input prices increase, import inputs are limited, food demand, food production, and output prices increase, food availability becomes the focus, local production sought after, imported products decreased, various marketing patterns varied, online order services and delivery order increased, marketing was increasingly creative, demand for fresh food increased, demand for processed food and household processing industries increased, prices for processed food increasing, processing innovations are increasingly diverse, online financing transactions, massive information dissemination, extensive sharing of agricultural experiences, price information increasing, multi-stakeholder meetings increasing, changes in agriculture policy. The research implication is that the Covid-19 pandemic provides an important lesson for agribusiness that agricultural is an important sector and the ability of business units to adapt and innovate is needed.